Kepemimpinan Transformasional, Keamanan Psikologis, dan Kompetensi TIK: Pengaruhnya terhadap Kinerja Karyawan - Siminto; Almaududi Ausat, Abu Muna; Shafiq, Muhammad Aqib; Judijanto, Loso; Azzaakiyyah, Hizbul Khootimah (Jurnal Pekommas, 2024)
In the growing digital era, transformational leadership has become one of the key factors in improving employee performance. It motivates employees to achieve organizational goals and creates a psychologically safe environment, where employees feel valued and supported. This study aims to examine the influence of transformational leadership and psychological safety on employee performance, by exploring the mediating role of ICT competence in Subang Regency MSMEs. This study employs a quantitative approach utilizing SEM-PLS methodology to explore the interrelationships among relevant variables. The research was conducted on 55 SMEs, using an online questionnaire as the data collection tool. This study emphasizes that ICT competence acts as a crucial mediating factor in the relationship between transformational leadership and psychological safety on employee performance in MSMEs in Subang Regency. The analysis results show that transformational leadership and psychological safety have a positive and significant impact on employee performance, which is enhanced by ICT competence. Transformational leadership improves employee performance by strengthening technical skills, technology knowledge, and the ability to adapt to new technologies. Similarly, psychological safety, supports employee performance through increased ICT competence, which facilitates productivity, work quality, and innovation.